PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN KAWANGKOAN UTARA - TENDA, PINGKAN; RARES, JOYCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: Organizational culture is a system of shared meanings embraced by members who emphasizeorganization with other organizations. Performance is the level of success in achieving goals. It is said that thesuccess of the goals as desired. Government apparatus is required to improve performance and develop. Theresearch method that writer use in this research is quantitative research method, With formulation of problem"whether there is change of organizational culture to performance of civil apparatus in sub-district ofKawangkoan Utara".Based on the result between organization with performance is 0,61, that is relation between two positive / strongvariable. And based on the significant results obtained t count> ttable or 4.07> 1.701 which means there is apositive and significant relationship between the organization with employee performance. While based on theresults of determination conducted by the company, the remaining 37.21% 62.79, by other factors not examinedin this study.Keywords: Organizational Culture, Performance of Civil State Apparatus